Composition, geometry, and emplacement dynamics of a large volcanic island landslide offshore Martinique: From volcano flank‐collapse to seafloor sediment failure?. (9th March 2016) - Brunet, Morgane; Le Friant, Anne; Boudon, Georges; Lafuerza, Sara; Talling, Peter; Hornbach, Matthew; Ishizuka, Osamu; Lebas, Elodie; Guyard, Hervé; ,
Abstract: Landslides are common features in the vicinity of volcanic islands. In this contribution, we investigate landslides emplacement and dynamics around the volcanic island of Martinique based on the first scientific drilling of such deposits. The evolution of the active Montagne Pelée volcano on this island has been marked by three major flank‐collapses that removed much of the western flank of the volcano. Subaerial collapse volumes vary from 2 to 25 km 3 and debris avalanches flowed into the Grenada Basin. High‐resolution seismic data (AGUADOMAR‐1999, CARAVAL‐2002, and GWADASEIS‐2009) is combined with new drill cores that penetrate up to 430 m through the three submarine landslide deposits previously associated to the aerial flank‐collapses (Site U1399, Site U1400, Site U1401, IODP Expedition 340, Joides Resolution, March–April 2012). This combined geophysical and core data provide an improved understanding of landslide processes offshore a volcanic island. The integrated analysis shows a large submarine landslide deposit, without debris avalanche deposits coming from the volcano, comprising up to 300 km 3 of remobilized seafloor sediment that extends for 70 km away from the coast and covers an area of 2100 km 2 . Our new data suggest that the aerial debris avalanche deposit enter the sea but stop at the base of submarine flank. We propose a new model dealing with seafloor sediment failures and landslide propagation mechanisms, triggered by volcanic flank‐collapse events affecting Montagne Pelée volcano. Newly recognized landslide deposits occur deeper in the stratigraphy, suggesting the recurrence of large‐scale mass‐wasting processes offshore the island and thus, the necessity to better assess the associated tsunami hazards in the region. Key Points: First drilling into submarine landslide deposits offshore volcanic island Large (300 km 3 ) submarine landslide deposit offshore Martinique comprises mainly deformed seafloor sediment, in a single frontally emergent morphology